Intraductal temperature-controlled radiofrequency ablation in malignant hilar obstruction: a preliminary study in animals and initial human experience - Kim, Eui Joo; Cho, Jae Hee; Kim, Yoon Jae; Lee, Tae Hoon; Kim, Joon Mee; Jeong, Seok; Kim, Yeon Suk (Endoscopy International Open, 2019)
Background and study aims Intraductal radiofrequency ablation (ID-RFA) is a recently developed method widely used for treatment of malignant extrahepatic biliary tract obstructions. However, its safety in hilar application has yet to be clearly demonstrated. The aim of this study was to evaluate the safety of ID-RFA in the treatment of malignant hilar obstruction.Patients and methods Endoscopic retrograde cholangiography followed by temperature-controlled ID-RFA at the hilar area using different probe lengths (11, 18, and 22 mm) and settings (7 or 10 W for 60 – 120 s) was performed in six mini-pigs. In addition, patients with malignant hilar obstruction who underwent palliative ID-RFA were retrospectively evaluated.Results In the animal study using different ID-RFA settings, post-ID-RFA fluoroscopic radiocontrast leakage and microscopic bile duct perforation with hepatic abscess were observed in four of the six mini-pigs. Only two of the them, in which an 11-mm ID-RFA probe at a target temperature of 80 °C, power of 7 W, and duration of 60 s was used, underwent successful ID-RFA without any immediate adverse events (AEs). Clinically, ID-RFA was performed using the 11-mm probe with the setting of 80 °C, 7 W, and 60 – 120 s for malignant hilar obstruction, and total of 11 patients underwent successful ID-RFA without AEs.Conclusions Our study suggests that ID-RFA performed using a short-length probe with settings of 80 °C, 7 W and 60 – 120 s is a safe and feasible palliative treatment for malignant hilar obstruction.